Lipophilicity and Interactions Properties of a Group of Thirteen Manzamenones in Comparison with Artemisinin and Quinine Using Quantum Chemical Methods: ONIOM and DFT (B3LYP) - KONE, Soleymane; ATSE, Adepo Jacques; DIOMANDE, Sékou; BAMBA, El-Hadji Sawaliho (European Journal of Applied Sciences, 2022)
This work was undertaken to determine and compare the lipophilic properties of a group of Manzamenones with those of two antimalarials (Quinine and Artemisinin). Manzamenones are atypical fatty acid derivatives, belonging to the large family of lipids. They are extracted from a marine sponge, of the genus Plakortis kenyensis, used in the treatment of malaria. Three approaches were used to estimate the lipophilicity values of the molecules. Secondly, we analyzed the intermolecular interactions between these molecules and each of the two probes: the water molecule and the 3-aminopropanoic acid molecule (alanine: a protein residue of the polymerase). Manzamenones are studied with a mixed method: ONIOM 2. The intermolecular interactions between Manzamenones and water are described at the B3LYP/6-31++G(d,p) level. The ones between Manzamenones and 3-aminopropanoic acid are described at B3LYP/6-31+G(d,p). The last part of the study was the determination of energetic parameters and the estimation of the relative stabilities of the complexes formed with the two probes. This part allowed making comparisons with Quinine or Artemisinin.